Revisiting The Theory Of Translation: Investigating The Translation Divan-e Hafiz - Kumar, Tribhuwan; Supriyatno, Triyo (Ijaz Arabi Journal of Arabic Learning, 2021)
Translation theory offers a complex phenomenon when source language (SL) is transported and communicated in the target language (TL). Therefore, it is a grave concern for a translator to utilize equivalent ideas in another language. The current investigation tried to analyze lexical collocations in Arabic literature poems from Divan-e Hafiz and compare interpretations made by A J. Arberry (1905–1969) and H. W. Clarke (1840-1905) in request to find the most widely recognized methods the two interpreters utilized and to uncover the benefits and imperfections relating to each technique. This paper investigated that strict, social, and semantic collocations are separately the most troublesome word mixes for interpreters to achieve the cycle. It further delineated that the most incessant methodology taken by the two interpreters was in the interpretation of the same word and, in a few cases, a decrease of the lexical relationship to limit contorting the structure, complex and semantic examples highlighted in poems while making a similar impact in the TL. This phenomenon provides an overview of how to teach Arabic literature translation well.